El Estado como capataz. Política ambiental, gobernanza y reterritorialización en el bosque tropical del Caribe mexicano - López Santillán, Ángeles A. (El Colegio de México A.C., 2021)
Environmental governance in Mexico has been mostly analyzed through emphasizing contentious actors and conflicts. Nevertheless, this perspective does not reveal the complex settings of environmental governance as regulatory framework for capital accumulation. In this article, I explain how the Mexican government arranged the conditions to stablish itself as the main actor and recipient of the program known as payments for ecosystem services of the forest. Through the state formation framework and over a case study, I try to reveal the real purposes behind this environmental policy, and how it works as an instrumental governance to attain and increase economic and political benefits for state power.